2020
DOI: 10.3389/fimmu.2020.01833
|View full text |Cite
|
Sign up to set email alerts
|

Podocytes Produce and Secrete Functional Complement C3 and Complement Factor H

Abstract: could therefore influence the local glomerular complement activation and regulation. This modulating effect should therefore be considered in all diseases where glomerular complement activation occurs. Furthermore, our data indicate a potential novel role of podocytes in the innate immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…We demonstrated the accumulation of C3 fragments including C3b, iC3b in whole kidney tissue homogenates and primary cell cultures of renal epithelial cells and pericytes (Figure 1). More recently, it was demonstrated that podocytes produce functional C3 and are a local source for glomerular complement activation (Muhlig et al, 2020). Our results using C3-deficient mice support a previous report of reduced fibrosis in these mice (X.…”
Section: C3 Fragments As Markers Of Complement Activation In Kidney Cellssupporting
confidence: 90%
See 1 more Smart Citation
“…We demonstrated the accumulation of C3 fragments including C3b, iC3b in whole kidney tissue homogenates and primary cell cultures of renal epithelial cells and pericytes (Figure 1). More recently, it was demonstrated that podocytes produce functional C3 and are a local source for glomerular complement activation (Muhlig et al, 2020). Our results using C3-deficient mice support a previous report of reduced fibrosis in these mice (X.…”
Section: C3 Fragments As Markers Of Complement Activation In Kidney Cellssupporting
confidence: 90%
“…We demonstrated the accumulation of C3 fragments including C3b, iC3b in whole kidney tissue homogenates and primary cell cultures of renal epithelial cells and pericytes (Figure 1). More recently, it was demonstrated that podocytes produce functional C3 and are a local source for glomerular complement activation (Muhlig et al, 2020). Our results using C3‐deficient mice support a previous report of reduced fibrosis in these mice (X. Zhou et al, 2013) but also extend this observation by showing that the lack of C3 expression in kidney tissue was accompanied by reduced deposition of active C3 fragments in the interstitial space and reduced infiltration of inflammatory cells, including macrophages.…”
Section: C3 Fragments As Markers Of Complement Activation In Kidney Cellsmentioning
confidence: 99%
“…CFAH, an abundant serum glycoprotein, is one of the most important circulating regulators of the alternative pathway. It is expressed constitutively in liver and locally expressed by endothelial cells, epithelial cells, and podocytes [ 33 ]. CFAH serves as an essential cofactor for CFAI-mediated C3b cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured immortalized human podocytes and primary human podocytes from a known Arg1182Ser (G3546T) CFAH mutant patient, CFAH was confirmed to be expressed by podocytes. Moreover, expression of CFAH was up-regulated in injured podocytes [ 33 ]. As a molecule of 150 kDa, CFAH is prevented from filtration by a healthy glomerular filtration barrier.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect would be lower if albumin reabsorption was disrupted (e.g., in nephrotic syndrome) ( 47 ). Moreover, several complement precursors are like albumin ligands for megalin-cubilin receptors and thus also undergo endocytic uptake, and tubular cells and podocytes can synthetize C3, which might add to intratubular C3 ( 48 , 49 ). Plasma albumin levels within the normal range indicate that liver synthesis function was intact.…”
Section: Discussionmentioning
confidence: 99%